Linguistic characteristics of AAC discourse in the workplace. (June 2013) - Friginal, Eric; Pearson, Pamela; Di Ferrante, Laura; Pickering, Lucy; Bruce, Carrie
This study examines linguistic co-occurrence patterns in the discourse of individuals with communication impairments who use augmentative and alternative communication (AAC) devices in the workplace by comparing them to those of non-AAC users in similar job settings. A typical workweek (≈ 40 hours) per focal participant (four AAC; four non-AAC) was recorded and transcribed to create a specialized corpus of workplace discourse of approximately 464, 000 words at the time of this analysis. A multidimensional analysis of co-occurrence patterns along functional linguistic dimensions, following Biber (1988, 1995) [ Variation across Speech and Writing . Cambridge: Cambridge University Press; Dimensions of Register Variation: A Cross-Linguistic Perspective . Cambridge: Cambridge University Press], reveals differences in the macro discourse characteristics of AAC vis-a-vis non-AAC texts. Results indicate that AAC texts make use of more informational, non-narrative, and explicit textual features of discourse than their non-AAC counterparts. Implications to improve the capabilities of AAC devices to produce speech that matches baseline expectations of co-workers in the workplace are discussed.